Imaging Findings of Extraventricular Neurocytoma: Report of 3 Cases and Review of the Literature - Yang, G.-F. (AJNR Am J Neuroradiol, 2009)
SUMMARY: Extraventricular neurocytoma (EVN) is rare entity with similar biologic behavior and histopathologic characteristics to neurocytomas that occur in the lateral ventricles, according to the 2007 World Health Organization classification. We report the cases of 3 patients with extraventricular neurocytoma, which presented as large tumors in the left frontal and parietal lobes and in the sellar region. MR imaging showed cystic degeneration, calcification and/or hemorrhage, intense enhancement, and perilesional edema. EVN should be considered in the differential diagnosis for large, heterogeneous, enhancing brain tumors that occur in young people.